AN ANALYSIS OF FEMALE LITERACY, WORK PARTICIPATION AND CHANGING ECONOMY IN INDIA. - RICHA SINGHAL, (International Journal of Psychosocial Rehabilitation, 2020)
Today the constantly change environment we can understand Education and Literacy as the two most important factors affecting the development of a nation and State. It is such an important development goal emphasized by nation out of the eight goals related to poverty, health, women empowerment, environment sustainability and Global Partnership for Development.In most of the sooner studies undertaken in India, it's been observed that gender disparities within the society cannot merely be explained in terms of their productivity, health, schooling or unequal buy work of equal importance. In spite of the very fact that within the Constitution of India women got equal the status its status is considered backward. Determinants of female literacy will vary from country to country, continent to continent, developed countries to developing countries and even within a rustic or state; it varies counting on the socioeconomic, demographic factors. Women constitute an integral a part of society and actively participate within the socio- economic development of a rustic. The status of girls in India has been subject to several changes over the past few decades.In various studies the status of female population in Rajasthan is discussed where the explanations for the backwardness of the feminine population are both cultural and economic. The study aimed to work out the connection of female literacy rate with the correlation of their participation in economic activities in Rajasthan especially in rural areas, their schooling, health condition, awareness, and medical facilities.With the objective author decided to investigate the contribution of female literacy by secondary data obtained from the Census-2001 and Census-2011 conducted by Government of India. Data for work participation and female literacy have been obtained from Census-2001 and Census-2011 of India. In order to find the relationship between variables coefficient of correlation have been used .The study concluded with the statement that literate women were more aware and careful about not only themselves but about their children and family as well in comparison to illiterate women. They were healthier, aware about family planning, child care etc indicating a clear relation between female literacy and work participation, hence the objective of the study to analyze the relationship between female literacy and their work participation in household industry, agriculture and cultivation are succeeded by the study.